International Law Material and Formal Fundaments for Republic of Serbia Criminal Code Article 268 in Practice - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2026)
Text "International law material and formal fundaments for Republic of Serbia Criminal Code Article 268 in practice", starting from the: At first place law science methods (Law normative method, Logic-normative, Formally normative method, Materially-normative method and Normative-hierarchically method), and at the second place elements of International law texts connected with the human rights as well as the problems of environment, explains substantial formal and material law elements which have to be respected and included in forming court decision on the possible injury of the Article 268 of Criminal Code in any concrete case.